Variation in Straw Grain Ratio and Straw Quality in Different Rice Cultivars of India - Das, Madan Mohan; Misra, Asim Kumar; Singh, Krishna Kunwar; Pailan, Gaur Hari; Khan, Tanveer Ahmed (Indian Journal of Animal Nutrition, 2019)
Straw grain ratio (S/G ratio) of paddy cultivars available across the country in different states was determined. Variation in straw quality was also estimated. Sampling locations were basically from farmers field spread over 9 major paddy producing states viz., Bihar, Chhatishgarh, Gujrat, Haryana, Jharkhand, Tamilnadu, Uttar Pradesh, Uttrakhand and West Bengal. A significant variation (P<0.001) in straw to grain ratio was recorded in among the paddy cultivars grown by the farmers in different states. Variability (P<0.05) within cultivar was also observed grown under different agro-climatic regions and agronomical practices. Similarly significant variations (P<0.01) in all quality attributes viz., CP,NDF, ADF, hemicelluloses, cellulose and lignin was recorded among the paddy cultivars. Among the various chemical constituents, the the lignin content varied greatly (126%) followed by CP(76.15%),hemicelluloses(72.34%), cellulose(37.67%),ADF (25.39%),and NDF(15.48%). The dry matter degradability of straw from different paddy cultivars ranged from 35 to 64.4 percent whereas fiber (NDF) digestibility varied from 63.52 to 80.74 percent. NBDMD was negatively correlated with ADF and lignin content of straw. It can be concluded that the variability in nutritional parameters among varieties /cultivars need to be exploited by plant breeders, particularly in paddy growing areas where paddy straw is a major roughage source for ruminant diet.